Easter parade - Berlin, Irving, 1888-; Berlin, Irving, 1888-; McCue, Lisa (New York : HarperCollinsPublishers, 2003)
In an illustrated version of the song, a little bunny and her father enjoy the Easter parade.
Keywords: Easter music; Songs; Rabbits -- Songs and music; Easter music; Children's music